2015
DOI: 10.1074/jbc.m114.635755
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GD3 Enhances Invasiveness of Gliomas by Forming a Complex with Platelet-derived Growth Factor Receptor α and Yes Kinase

Abstract: Background: Roles of GD3 in gliomas are not well understood. Results: PDGF receptor ␣ was identified as a GD3-associated molecule by enzyme-mediated activation of radical sources and mass spectrometry, and its association with GD3 and Yes leads to increased invasiveness. Conclusion: GD3 enhances invasiveness by forming a molecular complex. Significance: GD3/PDGF receptor ␣⅐Yes complex is a potential target for glioma therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 57 publications
1
55
0
2
Order By: Relevance
“…GD3 expression also resulted in the enhanced cell adhesion to various extracellular matrices (17). Involvement of increased phosphorylation of a Src kinase family, Yes, due to GD3, was also demonstrated in melanomas (18) and in gliomas (34).…”
Section: Discussionmentioning
confidence: 89%
“…GD3 expression also resulted in the enhanced cell adhesion to various extracellular matrices (17). Involvement of increased phosphorylation of a Src kinase family, Yes, due to GD3, was also demonstrated in melanomas (18) and in gliomas (34).…”
Section: Discussionmentioning
confidence: 89%
“…Therefore, the new potential biomarker for early diagnosis and novel therapeutic target needs to be explored. Although dozens of studies have indicated the complex gene interaction and molecular modulation network in the development of glioma, the research on revealing the oncogenes and tumor suppressors is still on the road [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…C‐2, C‐6, and C‐8 are GD2 − SK‐LC‐17 transfectants (Figures A, ). Tumor‐specific gangliosides coordinately work with plasma membrane proteins in cancer cells, which leads to enhancement of malignant phenotypes . However, it is not well known what kind of plasma membrane proteins work together with GD2 in SCLC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Although roles of GD2 in malignant phenotypes of SCLC have been analyzed, there is no information about molecules interacting with GD2 in GEM/rafts. To date, it has been reported that GD3 interacts with membrane proteins in melanomas and glioma cells, which promotes malignant phenotypes of individual cancer cells . In this study, we aimed to reveal the molecular mechanisms by which GD2 expressed on the membrane of SCLC cells induces malignant phenotypes, then used EMARS combined with MS to address this aim.…”
Section: Introductionmentioning
confidence: 99%